Design and functional optimization of a multi-feature coaster using petg-based additive manufacturing - F. Wijaya; D.W. Utama (Dinamika Teknik Mesin, 2026)
A coaster is a cup base designed to protect table surfaces from scratches and condensation drops from drinks. However, in their use, various problems are still encountered, such as low capacity to hold condensation drops, the lack of straw holders, and poor stability on slippery surfaces. This research used a product development method comprising three main stages: planning, design, and testing. This research aims to develop a more functional coaster design by adding several innovative features, namely a place to collect condensation drops, a hygienic straw holder, an anti-slip rubber layer, and a magnetic system to keep the handle and straw holder from coming off easily. The design process was carried out in Autodesk Inventor, then produced using FDM type 3D printing with Polyethylene Terephthalate Glycol (PETG) and laser cutting with acrylic. The base model of a coaster was derived from the Forgecore coaster, and the developed coaster was tested through several functional tests, including condensation container tests, glass stability, coaster stability, magnetic strength, and ease of use of additional features. The test results showed that all features functioned as designed and provided a significant performance improvement compared to the coaster made by Forgecore. Thus, this 3D-printed coaster design proves to be effective and feasible as an innovative product that supports daily work and study activities.